Identifying and Explaining Public Preferences for Renewable Energy Sources in Qatar - Ahmed K. Nassar (15612168) (2022)
As a major natural gas and oil producer, Qatar has made significant strides towards its energy transition. This paper uses a survey research design with statistical tests to investigate citizens' preferences for a wide range of energy resources. In this study, participants were asked to prioritize energy sources based on their environmental impact, price, benefits to Qatar's economy, support of energy security, and ability to create jobs. The results showed that approximately two-thirds of the sample (n = 354) preferred renewable energy sources, particularly solar, which ranks first. Renewable energy sources were more likely to be favored by the group with greater knowledge of energy sources than those with limited knowledge, except for solar energy, which was preferred by both groups. Additionally, both natural gas and wind rank second in terms of preference, followed by hydropower. In contrast, nuclear power was not ranked, indicating a strong opposition to this type of energy. The study provides an evidence-based example of the tendency of citizens in a hydrocarbon-rich country to prefer renewable energy sources and natural gas. The energy policymakers need to collaborate with local communities so that citizens can participate in important future energy discussions to develop a personal connection to climate solutions.  Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/   See article on publisher's website: http://dx.doi.org/10.3390/su142113835